Successful Completion of an International Project of the Department of Natural Sciences at New Bulgarian University - Pilarska, Daniela; Schafellner, Christa; Hoch, Gernot; Georgieva, Margarita; Georgiev, Georgi; Mirchev, Plamen (Annual of Natural Sciences Department, 2021)
The paper presents the results of a successfully completed international project of the Department of Natural Sciences titled â€œMonitoring and identification of the entomopathogenic fungus Entomophaga maimaiga in Lymantria dispar populationsâ€ and funded by the National Research Fund in 2017-2019. Investigating the distribution of E. maimaiga in Austria and Bulgaria in 2018-2019 shows that the pathogen has expanded its range to the west and reached Lower Austria. E. maimaiga has been identified in Bulgaria as well and has become part of the natural enemy complex of L. dispar.